Three-component synthesis of functionalized pyrrolo[3, 4-c]quinolin-1-ones by an unusual reductive cascade reaction. Issue 7 (18th February 2015) - Yu, Fu-Chao; Zhou, Bei; Xu, Hui; Li, Ya-Min; Lin, Jun; Yan, Sheng-Jiao; Shen, Yuehai
Abstract: We developed the first one-pot synthesis of structurally diverse pyrrolo[3, 4- c ]quinoline-1-one derivatives via a three-component cascade reaction of enaminones, amines, and isatin under acidic condition. This reaction proceeds through an unusual hydride transfer from in situ formed dimethylamine to a carbocation intermediate to generate the 3-methylene group. This method is straightforward, high-yield, easy to operate, and shows a broad substrate scope, thus potentially useful for diversity-oriented synthesis. Graphical abstract: